TYPES ET CARACTERISTIQUES DES JEUX DANS L'APPRENTISSAGE DES LANGUES («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article discusses the ways of using games in teaching foreign languages, the types and characteristics of educational games.
Keywords: learning process, educational games, communicative, creative and games developing speech competencies.